2009
DOI: 10.1093/eurjhf/hfp032
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of myocardial deformation and velocity dyssynchrony for identification of responders to cardiac resynchronization therapy

Abstract: AimsIt is unclear whether myocardial velocity or deformation indices of dyssynchrony are better at predicting response to cardiac resynchronization therapy (CRT). Therefore, two indices of left ventricular (LV) dyssynchrony based on myocardial velocity and deformation were compared to predict success of CRT. Methods and resultsSixty patients with dilated cardiomyopathy, New York Heart Association class III-IV, LV ejection fraction (EF) 35%, QRS .120 ms underwent CRT. The standard deviation of the averaged time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Although this result is in conflict with the study by Yu et al, 3 our findings are in line with more recent reports. Mele et al 19 report a comparison of tissue myocardial strain and velocity dyssynchrony and found that strain-derived regional timing of 12 nonapical segments better identified CRT responders. Likewise, Porciani et al 20 report a very low specificity of only 39% for the Tv-SD12 using a cutoff value of 33 milliseconds to predict response at the 6-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Although this result is in conflict with the study by Yu et al, 3 our findings are in line with more recent reports. Mele et al 19 report a comparison of tissue myocardial strain and velocity dyssynchrony and found that strain-derived regional timing of 12 nonapical segments better identified CRT responders. Likewise, Porciani et al 20 report a very low specificity of only 39% for the Tv-SD12 using a cutoff value of 33 milliseconds to predict response at the 6-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, when all the various echocardiographic measures of mechanical dyssynchrony were analyzed in a large, international multicenter study, no single measure proved capable of improving patient selection for CRT [87]. Promisingly, newer techniques including longitudinal myocardial strain assessment [88] and 3D speckle-tracking echo [89] appear more reliable and indicate an encouraging direction for future work.…”
Section: Dyssynchrony Assessment and Identification Of The Site Of Lamentioning
confidence: 99%
“…Our definition of CRT responder was in agreement with the standard criteria proposed by previous studies. Specifically, a positive response to resynchronization therapy was determined according to patient's functional status (defined as at least 1 class decrease of NYHA classification), cardiac performance (defined as relative increase in LV ejection fraction [EF] >20% from baseline) and reversing of LV remodeling (defined as more than 15% decrease of LV end‐systolic volume [LVESV]) 15–17 . To be qualified as a CRT responder, a patient had to fulfill at least 2 of the above 3 criteria.…”
Section: Methodsmentioning
confidence: 99%